Faktor-faktor yang Mempengaruhi Pengguliran Dana Pinjaman Program Sari Tani di Desa Tuabatan Kecamatan Miomaffo Tengah Kabupaten Timor Tengah Utara - Bryan Adrianus Matoneng; Werenfridus Taena (AGRIMOR, 2019)
This study aims to determine the factors that influence the rolling over of the Sari Tani Program loan funds in the Tuabatan Village of Central Miomaffo District. The research method is survey method with the sampling technique used is purposive sampling as many as 40 respondents. The data analysis used was descriptive qualitative analysis and logit analysis. The results showed that there were 5 groups that received initial funding to seek pig fattening and cattle paronization. The results also show that the use of factors that influence the rolling out of Sari Tani funds in the village of Tuabatan is membership status while age, income and communication have no effect on the overthrow of Sari Tani funds in the village of Tuabatan.